2011
DOI: 10.1083/jcb.201104062
|View full text |Cite
|
Sign up to set email alerts
|

Osh4p exchanges sterols for phosphatidylinositol 4-phosphate between lipid bilayers

Abstract: The yeast Kes1p/Osh4p protein functions as a sterol/PI(4)P exchanger between lipid membranes, which suggests the possibility of creating a sterol gradient via phosphoinositide metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
454
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(471 citation statements)
references
References 42 publications
17
454
0
Order By: Relevance
“…1b). These peaks are characteristic of DHE, which suggests fluorescence resonance energy transfer (FRET) from Upc2 LBD to bound DHE 25,26 . Upc2 LBD binds free DHE with nanomolar affinity as measured by equilibrium-binding experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). These peaks are characteristic of DHE, which suggests fluorescence resonance energy transfer (FRET) from Upc2 LBD to bound DHE 25,26 . Upc2 LBD binds free DHE with nanomolar affinity as measured by equilibrium-binding experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent measurements of DHE binding to Upc2 LBD were based on FRET between Trp and bound DHE and were carried out using methods as previously reported 26,53 . For kinetics measurements, Trp fluorescence was measured at 340 nm (bandwidth 5 nm) on excitation at 285 nm (bandwith 5 nm) in a spectrofluorometer (FP-6200; JASCO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies also implicate Osh proteins in nonvesicular sterol transportation (Raychaudhuri et al 2006;de Saint-Jean et al 2011;Jansen et al 2011). By measuring the amount of free sterols converted to steryl esters (esterification), Raychaudhuri et al showed a sevenfold decrease in total sterol transport from the PM to the ER in temperature-sensitive mutant yeast strains missing all seven Osh proteins.…”
Section: Er and Plasma Membranementioning
confidence: 99%
“…Osh proteins have previously been implicated in non-vesicular sterol trafficking between the ER and the PM, but recent work suggests an additional role of these proteins as phosphatidylinositol-4-phosphate (PI-4-P) sensors that modulate PI-4-P levels in the PM by regulating the ER-resident PI-4-P phosphatase Sac1 at the ER-PM contact sites (Stefan et al , 2011 ). A recent study of Drin, Antonny, and coworkers demonstrated that Osh4 binds sterols and PI-4-P in the same binding site and may, thus, generate a sterol gradient between the ER and the Golgi (de Saint -Jean et al, 2011 ). Such a behavior may apply to all sterol-binding proteins, which may use PIPs for their specific targeting and sterol delivery.…”
Section: Organellar Contact Zones As Novel Microcompartmentsmentioning
confidence: 99%